Breathwork sebagai Terapi Komplementer untuk Kecemasan dalam Konteks Wellness Tourism di Bali: Tinjauan Sistematis - Ni Putu Ayu Daneswari Dewi; Putu Adi Suputra; Kadek Listia Prasetya Dewi; Dewa Ayu Aryantika Anggraeni; Ni Nyoman Ayu Trisna Anggarini; Nyoman Ratih Widya Sari (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2026)
Introduction: Anxiety is a natural response to stress which, when excessive, can lead to psychological disorders. Conventional therapies such as pharmacotherapy and psychotherapy have not fully addressed the complexity of anxiety symptoms, leading to the development of breathwork as a complementary therapy. This review aims to evaluate the effectiveness of breathwork in reducing anxiety and to explore its potential role in supporting the development of wellness tourism based on holistic health in Bali. Method: This systematic review was conducted following the PRISMA guidelines through literature searches in PubMed, ScienceDirect, and Google Scholar databases. The included articles were original studies published between 2015 and 2025 that investigated the effectiveness of breathwork in reducing anxiety levels. Discussion: Based on the analysis of twelve selected articles, breathwork was found to be a significant complementary therapy for reducing anxiety. These findings also highlight its potential to be developed within the context of wellness tourism in Bali through the integration of breathwork practices as part of holistic health programs emphasizing mind–body balance. Conclusion: This review demonstrates that various forms of breathwork are consistently effective in reducing anxiety across different populations and hold potential for development within the framework of wellness tourism based on holistic health in Bali.